Scaling the Response of a Simplified Hull Girder Subjected to Underwater Explosions - Giovanni Marchesi; Luca Lomazzi; Marco Giglio; Andrea Manes (Engineering Proceedings, 2025)
Underwater explosions (UNDEXs) represent a significant threat to marine vessels, motivating the analysis of their resulting dynamic response and damage. Conducting experimental investigations on full-scale ships, while being the most consistent strategy, is not always feasible due to obvious economic constraints. Consequently, researchers usually rely on scaled models designed to replicate real-world scenarios in laboratory environments. Despite the widespread use of this approach, the scaling laws between prototypes and models are not yet satisfactory due to the complexity of the UNDEX phenomena and the variability in boundary conditions. To address this aspect, the present study focuses on the scalability of a simplified vessel, termed a simplified hull girder (SHG). This study is conducted numerically and originates from a comparison with experiments available in the literature. This work has two objectives: firstly, it provides a practical approach to simulating the behaviour of complex architectures that undergo severe deformation due to blast loads, a critical challenge for state-of-the-art computational methods. Secondly, this work aims to assess the reliability of the scaling laws commonly used in UNDEX scenarios and to highlight the importance of strain-rate effects.